(untitled) (IASH Indian Journal of Arid Horticulture, 2025)
Thirteen bael cultivars were evaluated for resistance to Alternaria leaf spot disease. Three cultivars were classified as resistant, nine as moderately resistant, and one as moderately susceptible. The disease prevalence was influenced by weather conditions, particularly temperatures ranging from 27.60°C to 35.75°C, relative humidity between 58.00% and 80.40%, 7.80 hours of daily sunshine and 1.50 mm of rainfall. The disease spread rapidly after seasonal rains, peaking during the 35th meteorological week with 60.60% intensity under temperatures of 24.95°C to 31.80°C and relative humidity of 74.05% to 90.25%. Among all the treatments, Propiconazole (@ 0.1%) was the most effective, reducing disease intensity (7.78%) and 71.41% disease control followed by Difenconazole (@ 0.1%) 10.69% disease intensity and 60.35% disease control, respectively.